TAMI-23. NEUTROPHIL-TRIGGERED FERROPTOSIS PROMOTES TUMOR NECROSIS IN GLIOBLASTOMA PROGRESSION - Yee, Patricia (Neuro Oncol, 2020)
Tumor necrosis indicates poor prognoses in many cancers, including glioblastomas (GBMs). Although thought to result from chronic ischemia, the underlying nature and mechanisms driving the involved cell death remain obscured by lack of animal models recapitulating the extent of necrosis in human GBMs. The molecular and clinical heterogeneity of GBMs adds further complexity. Not all GBMs contain necrosis. Mesenchymal (MES)-GBM, the subtype correlated with worst prognosis and highest treatment resistance, is most closely associated with necrosis. MES-GBM exhibits hyperactivity of transcriptional coactivator with PDZ-binding motif (TAZ), a Hippo tumor suppressive pathway effector whose expression in human GBMs predicts short survival. To elucidate mechanisms driving GBM necrosis, we devised a novel orthotopic mouse model recapitulating human MES-GBM phenotypically and histopathologically by expressing a constitutively-active TAZ mutant (TAZ(4SA)) in three human GBM cell lines (LN229, U87, and LN18) lacking MES signatures (GBM(4SA)). GBM(4SA) mice lived significantly shorter than mice implanted with GBM(vector) or mutant TAZ unable to bind its downstream effector, TEAD (GBM(4SA-S51A)). Extensive (≥30% of tumor volume) necrosis was present in GBM(4SA) mice but not GBM(vector) or GBM(4SA-S51A). In GBM(4SA) tumors, neutrophils coincide with necrosis temporally and spatially. Neutrophil depletion dampens necrosis. Neutrophils isolated from mouse tumors killed co-cultured tumor cells. Neutrophils induce iron-dependent accumulation of lipid hydroperoxides within tumor cells by transferring myeloperoxidase-containing granules into tumor cells. Inhibiting myeloperoxidase suppresses neutrophil-induced tumor cytotoxicity. Intratumoral glutathione peroxidase 4 (GPX4) overexpression or acyl-CoA synthetase 4 (ACSL4) depletion diminishes necrosis and aggressiveness of tumors. Human GBM analysis indicates neutrophils and ferroptosis are associated with necrosis and predict poor survival. Together, we propose that certain tumor damage(s) during early tumor progression (i.e. ischemia) recruits neutrophils to damaged tissue and results in a positive feedback loop, amplifying GBM necrosis development. We show GBM necrosis involves neutrophil-triggered ferroptosis and reveal an unprecedented pro-tumorigenic role of ferroptosis.